Rotor of a die-casting induction motor with anisotropic copper bars - Chuvashev, V. A.; Moukhametchine, N. A.; Gabdrakhmanov, Ch. (Національний технічний університет "Харківський політехнічний інститут", 2004)
Mathematical model describing the electromechanical processes in an induction motor with anisotropy copper bars is proposed. The model takes into account constructional features of explosion-proof induction motors. Results of its developing and bringing into production of unified series of the motors are presented.

Запропоновано математичну модель яка описує електромеханічні процеси у двигуні з анізотропною мідною кліткою. Модель ураховує особливості двигуна у вибуховозахищеному виконанні. Представлено результати розробки й впровадження уніфікованих конструкцій таких двигунів.
Keywords: induction motor; rotor; electromechanical processes; finite-element method; electromechanical converter; anisotropic copper bars